Infectious Aortitis: A Life-Threatening Endovascular Complication of Nontyphoidal Salmonella Bacteremia - Seifeldin Hakim; Francisco Davila; Mitual Amin; Ismail Hader; Mitchell S. Cappell (Case Reports in Medicine)
A 65-year-old Japanese man living in the United States presented with pyrexia and chills associated with intermittent lower abdominal and back pain for 5 days. He denied recent travel, rash, diarrhea, or rectal bleeding. Physical examination revealed spiking pyrexia, and routine laboratory tests revealed mild leukocytosis and neutrophilia. Abdominal CT with contrast showed findings highly compatible with aortitis. Comprehensive autoimmune evaluation was negative. Salmonella enterica serotype Enteritidis was isolated from blood cultures. IV antibiotics were administered, but the patient continued to experience low-grade pyrexia and mild leukocytosis, and follow-up abdominal CT showed progressive aortic inflammation. The patient therefore underwent resection of the affected aortic segment with in-situ graft replacement and lifelong suppressive antibiotics. The patient is asymptomatic with no complications at 18 weeks of follow-up. This case report illustrates that patients with infectious aortitis from nontyphoidal Salmonella may (1) present with nonspecific and nonlocalizing symptoms and signs except for sepsis; (2) have diagnostic blood cultures and abdominal CT findings; and (3) typically require aggressive, prolonged IV antibiotic therapy and surgery for potential cure of this life-threatening infection.